2015
DOI: 10.1111/1471-0307.12181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal variation on the properties of whipping cream, soft cheese and skim milk powder in the UK

Abstract: Whipping cream, skim milk powder and soft cheese were produced throughout the year. Whipping cream manufactured in spring and winter produced significantly higher overrun and better serum stability, and whipping time was related to buffering capacity of raw milk. Heat stability of reconstituted skim milk powder (RSMP) at 9% total solids (TS) was greater in summer and autumn, and >25% TS throughout the year. It was positively related to the protein content of raw milk, but negatively with fat. In contrast to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Some recent data (Chen et al . , ,b) on changes in composition of bulk milk in UK have been reported.…”
Section: Seasonal Variations Affecting the Composition Of Bovine Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent data (Chen et al . , ,b) on changes in composition of bulk milk in UK have been reported.…”
Section: Seasonal Variations Affecting the Composition Of Bovine Milkmentioning
confidence: 99%
“…However, whipping cream manufactured in spring and winter produced significantly higher overrun and better serum stability (Chen et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Due to the traditional animal feeding systems used in summer (pasture) and winter (silage and root crops) on small and medium-sized Polish farms, the season in which the milk is collected can alter the characteristics of the cheese produced from it. When analyzing dairy products manufactured using milk from a commercial dairy herd (UK), Chen et al [ 15 ] demonstrated that the season does not have a significant impact on the properties of soft cheese (apart from its hardness), which can therefore be produced throughout the entire year.…”
Section: Introductionmentioning
confidence: 99%